FRI0194 Is There an Association Between Spondyloarthritis and Antibodies Towards Borrelia, Ehrlichia and Chlamydia Species?. (9th June 2015) - Hermansen, L.T.; Loft, A.G.; Christiansen, A.A.; Gilbert, L.; Garg, K.; Karvonen, K.; Jurik, A.G.; Weber, U.; Manniche, C.; Jensen, T.S.; Arnbak, B.; Østergaard, M.; et al.
Abstract : Background: Several studies suggested that certain microorganisms might contribute to initiation and perpetuation of spondyloarthritis (SpA). Objectives: To investigate IgG and IgM antibodies towards Borrelia burgdorferi (Bb), Borrelia garinii (Bg), Borrelia afzelii (Ba), Ehrlichia spp. (Ehr), Chlamydia trachomatis (Ct), and Chlamydia pneumoniae (Cp) in SpA patients, low back pain patients, and healthy subjects and to elucidate whether previous infections could play a role in the onset of SpA. Methods: Data collection was based on persons aged 18-40 years referred with low back pain for ≥3 months. They were examined with MRI of the spine and sacroiliac joints, CRP, HLA-B27, and clinical SpA features were assessed according to ASAS classification criteria (1). Sera were collected from patients with SpA according to ASAS criteria (SpA group; n=100), persons with low back pain but with a positive MRI or positive HLA-B27 and one clinical SpA feature (suspected (susp.) SpA group; n=41), and low back pain patients having no SpA features (LBP group; n=82). These groups were compared with age and gender matched healthy controls (n=40). With ELISA-tests, levels of IgG and IgM antibodies towards Bb, Bg, Ba, Ehr, Ct, and Cp were investigated and compared between groups. Mann-Whitney U test was used for comparing antibody levels between groups, and Spearman's test with Bonferroni correction for correlation analysis between antibodies and characteristics such as age, gender, HLA-B27 status, CRP, recent onset back pain (<1 year), and positive X-ray (according to modified New York criteria). Results: Levels of IgG and IgM antibodies towards Bb, Bg, Ba, and Ehr were significantly elevated in the SpA, susp. SpA, and LBP groups compared to healthy controls (p<0.01, p<0.001). Significant elevations of IgG towards Bg and Ba were observed in the SpA group compared to LBP group (p<0.05). IgG towards Ct was elevated in susp. SpA group compared to healthy controls (p<0.05), and IgM to Cp was elevated in susp. SpA and LBP groups compared to healthy controls (p<0.01). Correlation analysis between levels of antibodies and characteristics such as age, gender, HLA-B27 status, CRP, recent onset back pain (<1 year), and X-ray did not show any statistic significance. Conclusions: Our results suggest that the elevated levels of antibodies towards Borrelia, Ehrlichia and Chlamydia species in patients with prolonged chronic low back pain are not related to SpA, and require other explanations. References: Rudwaleit M et al., Ann Rheum Dis. 2009;68(6):777-83. Disclosure of Interest: None declared